Weight-Related Selves and Their Relationship With Body Mass Index Among Young Individuals in Curaçao. (May 2019) - Dijkstra, Pieternel; Van Brummen-Girigori, Odette; Barelds, Dick P. H.
Based on the assumptions of self-discrepancy theory, the present study examined the degree of overweight, weight-related body images, and the relation between these images and body mass index (BMI) among two samples of young people from Curaçao (secondary school students, n = 176; undergraduate students, n = 205). In addition to BMI, participants reported their current, ideal, and most feared body sizes, the thinnest and largest body sizes still acceptable to them, and the body size they considered the healthiest by means of the Contour Drawing Rating Scale. We expected females to show a larger discrepancy between current and ideal body size than males (Hypothesis 1) and that this discrepancy (as an indicator of body dissatisfaction) would be related more strongly to BMI among females than among males (Hypothesis 2). Results yielded support for Hypothesis 1 among secondary school students only. Only in the undergraduate sample, BMI and body dissatisfaction were related, but equally so for males and females. Possible explanations are discussed as well as implications for weight management interventions.